Analysis on the Influence of Increasing Seismic Fortification Intensity on Seismic Performance of Underground Station - Ying Zeng; Shiguang Xu; Shiqian Yin (Advances in Civil Engineering)
China Earthquake Parameter Zoning (2016) has increased the seismic fortification intensity in Chengdu from VII to VIII. It is necessary to conduct in-depth discussion on the impact of the seismic performance of the built underground station structure. In this paper, a stratum-structure finite element model is established with a Chengdu subway station as an example. The model boundary adopts viscoelastic boundary, and the ground motion is input in the form of equivalent nodal force. The equivalent linearization method is used to consider the nonlinearity of soil materials. The time-history analysis of seismic fortification intensity of VII and VIII degrees is carried out, respectively. By comparing the calculation results of the two seismic fortification intensity ground motion conditions, it is concluded that the connection between the side wall and the floor is the weakest position of the station structure under the action of the earthquake; the seismic fortification intensity is increased from VII to VIII to the internal force of the structure. It has a relatively large impact, especially the most obvious impact on the bending moment. The results of the verification of the seismic time-history analysis show that the increase of fortification intensity will have a more obvious impact on the structural deformation, and the structural design of the station can meet the safety performance requirements of VII and VIII degrees of seismic fortification. The research has certain reference significance for the seismic safety evaluation of the built underground station structure in Chengdu area.